Re-theorising namûs beyond ‘honour’: self-making, feminist agency and global epistemic justice - Cetinkaya, Hasret (Feminist theory, 2025)
Namûs describes a ‘way of life’ integral to Kurdish sociality and to the sense of self for many Kurds who live it in a plurality of ways. Constituting a form of power over the subject which can potentially take the form of domination, namûs is also a social relation of care and power between subjects and is integral to its subject's ethical relationship of self-to-self and processes of self-making. Post-Enlightenment and liberal frameworks of ‘modern’ selfhood, however, have tended to render namûs equivalent to ‘honour’ and ‘honour-based violence’ (‘HBV’). Through this act of mistranslation, a life with namûs is constructed as violent, unworthy, racially inferior and harmful to women. Building upon multi-sited ethnographic fieldwork conducted in North Kurdistan, Turkey and Denmark, this article originally theorises namûs as a practice of ethical self-making that is epistemic, dignified and agentic in all its complexities. Women living with and through namûs actively work to cultivate this way of being, thereby interrupting the epistemic authority of liberal feminism. Namûs, this article argues, cannot be understood through blanket explanations of ‘crime’, ‘oppression’ and ‘patriarchy’, as the discourse on ‘honour’ would suggest. Breaking away from these injurious portrayals is, therefore, vital to realise global epistemological justice.